Correlational Study of Culturally-Based Instructional Strategy and Cognitive Competencies on Problem Solving, Speaking and Listening: An Evidence in Oyo State Nigeria - Oluyemisi Majebi; Esther Oduolowu (International Journal of Emerging Issues in Early Childhood Education, 2021)
The study examined the impact of culturally based Instructional strategy (indigenous songs, rhymes, games, stories, language of the immediate environment and instructional materials) on pre-primary school children’s cognitive competence with special attention to problem-solving, speaking and listening skills. Socio-cultural theory provided the framework, while pretest-posttest control group quasi-experimental design was adopted. 74 children (44 males and 30 females) with a mean age of 5.61 from four pre-primary schools (two public and private schools) were purposively selected from two local government areas, and randomised into CIBS and conventional groups respectively. Children’s Cognitive Competence Rating Scale (r = 0.89) and CBIS Instructional Guide were used to collect the study data. Paired sample t-test and Analysis of covariance(ANCOVA) were used to analyse the data. There was a significant main effect of treatment on children’s cognitive competence (F(1,65) = 10.31; partial ?2 = 0.14). CIBS was found to be potent in enhancing pre-primary school children’s cognitive competence, especially in problem-solving, speaking, and listening skills. Teaching and learning activities at the pre-primary school level should employ a culturally-based instructional strategy.